The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1007/s10531-016-1093-y
|View full text |Cite
|
Sign up to set email alerts
|

Scale- and taxon-dependent patterns of plant diversity in steppes of Khakassia, South Siberia (Russia)

Abstract: The drivers of plant richness at fine spatial scales in steppe ecosystems are still not sufficiently understood. Our main research questions were: (i) How rich in plant species are the natural steppes of Southern Siberia compared to natural and semi-natural grasslands in other regions of the Palaearctic? (ii) What are the main environmental drivers of the diversity patterns in these steppes? (iii) What are the diversity–environment relationships and do they vary between spatial scales and among different taxon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
53
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 50 publications
(70 citation statements)
references
References 60 publications
(121 reference statements)
10
53
7
Order By: Relevance
“…The superiority of the power function has also been shown at similar grain sizes and in continuous vegetation as well as habitats other than grasslands (e.g. Moreover, power function SARs provide, with their exponent (z-value), a meaningful (and standardized) beta-diversity measure in continuous vegetation (Jurasinski et al, 2009;Polyakova et al, 2016), enabling the effective comparison of species turnover among taxa or between different ecological conditions. This leads us to conclude that the power function is a suitable (and mostly the best possible) model for SARs in nearly any situation, provided the areas from which the relationship is constructed are contiguous.…”
Section: Discussionmentioning
confidence: 96%
“…The superiority of the power function has also been shown at similar grain sizes and in continuous vegetation as well as habitats other than grasslands (e.g. Moreover, power function SARs provide, with their exponent (z-value), a meaningful (and standardized) beta-diversity measure in continuous vegetation (Jurasinski et al, 2009;Polyakova et al, 2016), enabling the effective comparison of species turnover among taxa or between different ecological conditions. This leads us to conclude that the power function is a suitable (and mostly the best possible) model for SARs in nearly any situation, provided the areas from which the relationship is constructed are contiguous.…”
Section: Discussionmentioning
confidence: 96%
“…In addition to vascular plants, dry grasslands of the class Koelerio-Corynephoretea can also harbour high diversity of bryophytes and lichens . Although recent publications on grassland diversity have largely focused on semi-natural grasslands (Chytrý et al 2015, there is some evidence that also natural Palaearctic steppes, which are still very much understudied, could be extremely rich in small grain sizes (Polyakova et al 2016).…”
Section: Eurasian Steppes and Dry Grasslandsmentioning
confidence: 99%
“…Since they resemble ecologically and floristically the meadow steppes of the forest steppe zone in Eastern Europe and Middle Asia one might wonder why equally high or even higher small-scale richness values are not found in the natural meadow steppes. This Special Issue contains two contributions that applied standardised EDGG multi-scale phytodiversity sampling (Turtureanu et al 2014) for the first time in natural steppe vegetation: Kuzemko et al (2016) in Central Podolia, Ukraine, a part of the forest-steppe zone of the European steppe region, and Polyakova et al (2016) for Khakassia, Russia, at the transition from the Middle Asian to the Mongolian region. Both author teams found high vascular plant species richness across spatial scales, with maxima, however, that were below the maxima in semi-natural grasslands of Central Europe.…”
Section: Patterns and Drivers Of Biodiversitymentioning
confidence: 99%
“…Across the Siberian and Central Asian steppes, the Virgin Lands Campaign of the Soviet Union led to Fig. 1 Simplified map of the Palaearctic steppe biome (with main steppe ecoregions after Wesche et al 2016) with localisation of the studies included in this Special Issue: (1) Kuzemko et al (2016); (2) Polyakova et al (2016); (3) Sutcliffe et al (2016); (4) Dembicz et al (2016); (5) Kajtoch et al (2016); (6) Weking et al (2016); (7) Mathar et al (2016); (8) Lameris et al (2016); (9) Wang and Wesche (2016); (10) Addison and Greiner (2016); (11) Niu et al (2016); (12) Novenko et al (2016); (13) Deák et al (2016); (14) Ambarlı et al (2016); (15) Kamp et al (2016); (16) Brinkert et al (2016); (17) Kämpf et al (2016). Reviews summarising data across countries are indicated by large asterisks (i.e.…”
Section: Introductionmentioning
confidence: 99%